Gendering the International Asylum and Refugee Debate - Freedman, J. author. aut Link
VIII, 246 p.
Keywords: This revised and updated 2nd edition of Freedman's hard-hitting study aims to remedy the current lack of gender-specific analyses of asylum and refugee issues. It provides a comprehensive account of the situation of women in global forced migration, and explains the ways in which women's experiences are shaped by gendered relations and structures.